ANALISIS RASIO KEUANGAN DALAM MENILAI KINERJA KEUANGAN PT. UNILEVER INDONESIA - Firna, Lira; Hasyim, Sitti Hajerah; Azis, Hariany (Universitas Jabal Ghafur, 2024)
This research aims to find out what the liquidity ratio is. able to measure financial performance at PT. Unilever Indonesia. The type of research used in this research is a quantitative descriptive approach. The data processed are reports of financial position and profit and loss for the period 2019 to 2022 which were obtained from PT's annual report. Unilever Indonesia Tbk. The calculation technique used in this research is calculating the percentage of liquidity ratio. Meanwhile, the data analysis technique used in this research is calculating the current ratio, quick ratio and cash ratio. The results of calculations and data collection on PT's financial performance. Unilever Indonesia, which is listed on the Indonesia Stock Exchange, can be concluded that the company's financial condition is in an illiquid condition because it can be seen from the calculation of the average current ratio of 0.63 times, meaning that only 63 rupiah of current assets can cover 100 rupiah of current debt, the average ratio The cash ratio is 0.44 times, which means that only 44 rupiah of current assets can cover 100 rupiah of current debt without taking into account the stock value, and the average cash ratio is 0.05 (5%) meaning cash is not yet able to finance current debt.